Dynamics of Generalized Tachyon Field in Teleparallel Gravity - Behnaz Fazlpour; Ali Banijamali (Advances in High Energy Physics)
We study dynamics of generalized tachyon scalar field in the framework of teleparallel gravity. This model is an extension of tachyonic teleparallel dark energy model which has been proposed by Banijamali and Fazlpour (2012). In contrast with tachyonic teleparallel dark energy model that has no scaling attractors, here we find some scaling attractors which means that the cosmological coincidence problem can be alleviated. Scaling attractors are presented for both interacting and noninteracting dark energy and dark matter cases.